Fundações de torres de lInhas de transmissão e de telecomunicação - Ronaldo Azevedo Chaves (2004)
This text gathers the necessary information to the design of foundations of transmission lines towers and telecommunications towers, collected by the author during his workinglife in structure design. The origin and nature of the loads applied to the structure which has the foundations as support are studied here. This text also brings basic information about geology and geotechnical enginnering that helps to know the soil behavior under the loadings of these special foundations. The design process to each one of the main type of foundations used nowadays is presented here. The steps to the working up of project with all the activities involved in the process are presented: the line profile analysis, the soil information analysis, the study about the tower type and the load combinations, the choice of foundation and, finally, the project. The text is intended to provide information not only to the foundation designer engineer, but also to geotechnicians, electrical engineers and electrical engineers of telecommunication, that take part in the project. This explains the use, in many parts of the text, of a simple technical language, that all these professionals can understand. For thesame reason, much information, essential for the foundation designer engineer, were kept.